Oxidized cellulose-based hemostatic materials. (15th February 2020) - Zhang, Shaohua; Li, Jiwei; Chen, Shaojuan; Zhang, Xiying; Ma, Jianwei; He, Jinmei
Highlights: The oxidation, origin, and biodegradability of oxidized cellulose are reported. The application of oxidized cellulose for hemostatic materials is described. Various forms of oxidized cellulose-based hemostatic materials are discussed. Modification of oxidized cellulose-based hemostatic materials is introduced. Abstract: The application of hemostatic agents is essential to prevent significant blood loss and death from excessive bleeding in surgical or emergency scenarios. Oxidized cellulose is an excellent biodegradable and biocompatible derivate of cellulose, which has become one of the most important hemostatic agents used in surgical procedures. However, to date, there has been no comprehensive report assessing oxidized cellulose-based hemostatic materials. Hence, this paper first reviewed the oxidation preparation, cellulose origin and structure, as well as biodegradability and safety of oxidized cellulose. Then a comprehensive review regarding the hemostatic mechanisms, various forms, modification, and current commercially available products of oxidized cellulose is discussed, which emphatically presents the most significant developments in the recent scientific literature. In conclusion, this paper summarizes the latest developments in oxidized cellulose-based hemostatic materials and provides a reference for further research and development in this field.